Effects of anti-osteoporotic drugs in patients with chronic kidney disease: a systemic review and network meta-analysis of bone mineral density, clinical fracture rate and renal function - Wung, Chih-Hsuan; Liu, Hao-Yu; Tsai, Tsung-Ting; Chen, Jia-Jin (Frontiers in Pharmacology, 2025)
ObjectiveThis systematic review and network meta-analysis investigated the effects of various anti-osteoporotic drugs (AODs) on bone mineral density (BMD), estimated glomerular filtration rate (eGFR), and clinical fracture rate in patients with chronic kidney disease (CKD) and osteoporosis.Methods and resultsWe searched for relevant studies in PubMed, Embase, and Web of Science and included randomized controlled trials with any following outcomes of interest: clinical fracture rate, BMD, and eGFR. The effectiveness of different AODs was assessed by random-effects model network meta-analysis and ranked on the basis of P-scores. A total of seven studies involving 18,503 patients were included. Three AODs: sclerostin inhibitors, bisphosphonates and parathyroid hormone (PTH) analogs were associated with mild but significantly increased BMD at the lumbar spine, total hip, and femoral neck. In addition, sclerostin inhibitors (relative risk; RR:0.38, 95% CI: 0.23–0.62), bisphosphonates (RR:0.53, 95% CI: 0.30–0.92), denosumab (RR:0.58, 95% CI: 0.52–0.66), and PTH analogs (RR:0.68, 95% CI: 0.55–0.86) effectively reduced clinical fracture rates. AODs did not significantly affect eGFRs. Among the five AODs, according to P-score ranking, sclerostin inhibitors were the most effective in reducing clinical fracture risk, and PTH analogs resulted in the most favorable improvement in BMD. The five AODs had no significant effect on eGFR.ConclusionWe demonstrated that bisphosphonates, PTH analogs, denosumab, and sclerostin inhibitors can reduce clinical fracture risk in CKD patient’s osteoporosis but with low to very low confidence of evidence. In clinical practice, sclerostin inhibitors and PTH analogs could result in the highest reduction in clinical fracture risk and improvement in BMD, respectively.